Effects of fucoidan on growth performance, immunity, antioxidant ability, digestive enzyme activity, and hepatic morphology in juvenile common carp (Cyprinus carpio) - Li, Fang; Sun, Hanchang; Li, Yang; He, Die; Ren, Chaoying; Zhu, Chengke; Lv, Guangjun (Frontiers in Marine Science, 2023)
The present study was conducted to investigate the influences of feeding fucoidan on growth performance, biochemical indices, immunity, antibacterial ability of plasma, digestive enzyme activity of intestine, antioxidant capacity and histological structure of liver in juvenile common carp. Five experimental diets added with 0 (Diet 1), 500 (Diet 2), 1000 (Diet 3), 1500 (Diet 4), and 2000 (Diet 5) mg/kg fucoidan, were fed to triplicate groups of 30 fish (35.83 ± 0.24 g) respectively for 8 weeks. The results exhibited that fish fed the diets with fucoidan supplementation of 1666.67 1757 mg/kg might be the best growth performance (P < 0.05). The levels of plasma total protien (TP) and albumin (ALB) in Diet 3, Diet 4 and Diet 5 were higher than in Diet 1 and Diet 2 (P < 0.05). Besides, the contents of plasma C3, LYZ and IgM, the antibacterial ability of serum, and the activity of SOD, CAT, POD, GPX in liver, ACP, AKP, LPS, AMS and TRY in intestine were significantly improved, and the contents of LPO and MDA in liver were notably decreased in diets with fucoidan supplement (P < 0.05). Furthermore, the activity of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) and the contents of total bilirubin (TB) and glucose (Glu) in Diet 5 were the highest among the groups. Meanwhile, the proinflammatory factor (plasma IL-6 and IL-1β) were higher expression, but the anti-inflammatory factor (plasma IL-1) was lower expression in Diet 5 (P > 0.05). It indicated that a higher dose (2000 mg/kg) of fucoidan may be induce inflammation and metabolic disorders. Interestingly, histological results of liver also indicated that dietary fucoidan intake a certain content (500 1500 mg/kg) could ameliorate hepatic morphology, but the high dosage (2000 mg/kg) probably caused damage to the liver contrarily. To the best of our knowledge, this is the first study on the application of fucoidan as a functional additive to juvenile common carp. The results of present study could be used to guide the application of fucoidan in the healthy aquaculture, and could further reveal the effect and mechanism of fucoidan on the nutritional physiology of aquatic animal.